Viscosol Treatment Ameliorates Insulin-Mediated Regulation of Dyslipidemia, Hepatic Steatosis, and Lipid Metabolism by Targeting PTP1B in Type-2 Diabetic Mice Model - Idrees Raza; Aamir Sohail; Hamza Muneer; Hajra Fayyaz; Zia Uddin; Amany I. Almars; Waheeb S. Aggad; Hailah M. Almohaimeed; Imran Ullah (International Journal of Endocrinology)
Type 2 diabetes mellitus (T2DM), a metabolic disorder, has the hallmarks of persistent hyperglycemia, insulin resistance, and dyslipidemia. Protein-tyrosine phosphatase 1B (PTP1B) was found to be overexpressed in many tissues in the case of T2DM and involved in the negative regulation of insulin signaling. So, PTP1B inhibition can act as a therapeutic target for T2DM. Numerous studies claimed the anti-inflammatory, hypoglycemic, hepatoprotective, and hypolipidemic activities of Dodonaea viscosa. Previously, we generated the high-fat diet (HFD)-low dose streptozotocin (STZ)–induced diabetic male mice model and treated it with a PTP1B inhibitor (5, 7-dihydroxy-3, 6-dimethoxy-2- (4-methoxy-3- (3-methyl-2-enyl) phenyl)-4H-chromen-4-one), isolated from Dodonaea viscosa. In the current study, we aimed to investigate the De novo lipogenesis, adipocyte differentiation, augmentation of lipoproteins clearance, fatty acid uptake, antilipolysis activity, and hepatic steatosis of PTP1B inhibition in adipose and liver tissues of the HFD-STZ–induced diabetic mice model. We found the retrieval of normal morphology of adipocytes and hepatocytes in the compound-treated group. The biochemical parameters showed the gradual reduction of LDL, VLDL, TC, and TG in the serum of the compound-treated group. To further test our hypothesis, real-time PCR was performed, and data revealed the reduction of PTP1B and other inflammatory markers in both tissues, showing enhanced expression of insulin signaling markers (INSR, IRS1, IRS2, and PI3K). Our compound upregulated the adipogenic (PPARγ), lipogenic (SREBP1c, FAS, ACC, and DGAT2), lipoprotein clearance (LPL, LDLR, and VLDLR), fatty acid uptake (CD36 and FATP1), and lipid droplet forming (FSP27 and perilipin-1) markers expressions in adipocytes and downregulated in hepatocytes. Furthermore, we found elevated cholesterol efflux (in adipose and liver) and decreased lipolysis in adipocytes and elevated in hepatocytes. Hence, we can conclude that our compound protects the adipocytes from abrupt lipolysis and stimulates adipocyte differentiation. In addition, it plays a hepatic protective role by shifting clearance and uptake of lipoproteins and fatty acids to the peripheral tissues and retrieving the fatty liver condition.